The impact of B‐cell‐directed therapy on SARS‐CoV‐2 vaccine efficacy in chronic lymphocytic leukaemia. (18th February 2022) - Ujjani, Chaitra; Shadman, Mazyar; Lynch, Ryan C.; Tu, Brian; Stevenson, Philip A.; Grainger, Caitlin; Zhu, Haiying; Hill, Joshua A.; Huang, Meei‐Li; Nielsen, Leslie; Poh, Christina; Sorensen, Tyler; et al.
Abstract: Prior reports evaluating SARS‐CoV‐2 vaccine efficacy in chronic lymphocytic leukaemia (CLL) used semiquantitative measurements of anti‐S to evaluate immunity; however, neutralization assays were used to assess functional immunity in the trials leading to vaccine approval. Here, we identified decreased rates of seroconversion in vaccinated CLL patients and lower anti‐S levels compared to healthy controls. Notably, we demonstrated similar results with the Roche anti‐S assay and neutralization activity. Durable responses were seen at six months; augmentation with boosters was possible in responding patients. Absence of normal B cells, frequently seen in patients receiving Bruton tyrosine kinase and B‐cell lymphoma 2 inhibitors, was a strong predictor of lack of seroconversion.